The use of double-subgenomic Sindbis virus transducing systems as tools for understanding virus-vector interactions - Cirimotich, Christopher Michael, author; Olson, Kenneth, advisor (Colorado State University. Libraries, 2008)
Recombinant Sindbis viruses (SINV) have been developed that express foreign sequence from an engineered viral promoter. These SINVs are valuable tools for studying virus interactions with mosquito vectors. Currently, transducing systems constructed from the genomes of SINV strains TE12 and MRE16 allow researchers to study molecular determinants of virus infection in mosquitoes and manipulate endogenous pathways in multiple invertebrate species. However, many aspects of arbovirus transmission cycles including interaction of the infecting virus with the mosquito immune response and virus transmission to the vertebrate host remain incompletely characterized. Novel double-subgenomic systems were constructed to further study SINV interactions with the Aedes aegypti mosquitoes and develop new tools to analyze aspects of the Sindbis virus transmission cycle. A TE 12-based transducing system has been engineered to express Flock House virus protein B2, a known inhibitor of RNA interference (RNAi). Here I show that RNAi modulates SINV infection of Ae. aegypti mosquitoes and that the virus can become pathogenic when the vector's RNAi response is suppressed. RNAi may be necessary for persistent arbovirus infection of the mosquito vector. The mechanism of virus-induced gene silencing was examined in cell culture using SINVs expressing sequence of an endogenous mosquito gene (lysozyme) in sense or antisense orientation. TE12-based transducing systems can efficiently mediate silencing of lysozyme expression but MRE 16 systems cannot. The MRE 16 system does elicit production of siRNAs, the hallmark of RNAi-mediated silencing, but to a much lesser degree than the equivalent TE12 system. To improve on existing transducing systems, a panel of MRE16 viruses was constructed to express fluorescent and bioluminescent proteins to be used as markers of virus infection. Also, a TE12 virus with potential targeted infection capabilities was engineered. Although the functionality of the targeted virus could not be shown, the range of experiments that can be performed using SINV systems has been expanded. Together, this work provides insight into the interactions between SINV and the mosquito RNAi response, characterizes the use of SINV for RNAi-mediated silencing studies, and has produced viruses that can be used to better understand the molecular mechanisms of SINV infection of and transmission by the mosquito vector.
Keywords: Sindbis virus; transducing systems; virus-vector interactions; virology